CONTEXTUAL INTELLIGENCE AMONG UNIVERSITY STUDENTS - Assist. Prof. Dr. Rashid Nasir Khalifa, Assist. Lect. Zamn Rahi Awdah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims at identifying: - 1- The average degree of contextual intelligence among university students. 2- The contextual intelligence of university students according to the variables of gender (male and female), specialization (scientific-human), stage (third, fourth). By the random stratified method of proportional distribution, the current research sample was selected, as it reached (400) male and female students from Wasit University.